2016
DOI: 10.1080/02670836.2016.1180752
|View full text |Cite
|
Sign up to set email alerts
|

Properties and microstructure of double-sided friction stir-welded microalloyed steel

Abstract: This study investigated the properties and microstructures of EH46 microalloyed steel following double-sided friction stir welding. The partially welded material was reversed, completing the weld. Yield strength, elongation and toughness of the weld were similar to those of the base material. During welding, the ferrite-pearlite in the base material transformed to mainly upper bainite, but the overlap or interference zone in the centre of the weld consisted predominantly of 0.5-3 µm recrystallised ferrite grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…These include the possible retention of some transition metal carbides-25 to 100 nm in size, identified in BM, in the IZ, and an understanding of the role they have in developing the microstructure of IZ. Also, if, as was proposed, [10,15] the FSW temperature associated with IZ was below Ac 1 , and below Ac 3 during TMAZ formation, then it is important to understand the dissolution of pearlite in the banded BM during the processing, and in what form that carbon assumes in the weld zone.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These include the possible retention of some transition metal carbides-25 to 100 nm in size, identified in BM, in the IZ, and an understanding of the role they have in developing the microstructure of IZ. Also, if, as was proposed, [10,15] the FSW temperature associated with IZ was below Ac 1 , and below Ac 3 during TMAZ formation, then it is important to understand the dissolution of pearlite in the banded BM during the processing, and in what form that carbon assumes in the weld zone.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Several publications describe the results of this double-sided FSW technique for steels. [10,14,15] The study reported in Reference 10 investigated the dominant deformation mechanisms by looking at the evolution of microstructure and crystallographic texture in different regions of the weld, but has not considered in detail the evolution of microstructure at submicron scales.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations